Factors Influencing Financing of Small and Medium Enterprises in the Banking Sector - Jahra Maulida; Afif al Mubarak; Aprilian Luchiansyah; Dinni Ramalia; Hasanatul Fadhli; Rohenza Marta Sukma (CV. Doki Course and Training, 2025)
Financing is a critical factor affecting the growth and success of small and medium enterprises (SMEs). In the banking sector, financing small and medium enterprises plays an important role in enhancing the economic competitiveness of a country. However, SMEs often experience difficulties in accessing financing from financial institutions, resulting in bottlenecks in their development. This study aims to analyze the factors that influence the financing of small and medium enterprises in the banking sector. The factors can be divided into two categories, namely internal factors and external factors. Internal factors include the quality and performance of SMEs, such as profit, growth, stability, and capitalization. In addition, the characteristics of SME owners, such as experience, education, and ownership of equity capital, also affect access to financing from the banking sector. On the other hand, external factors, such as banking regulations, market conditions, and government policies, also affect the financing of small and medium enterprises in the banking sector.This study uses a secondary data analysis method. Data was obtained from banking institutions and related financial institutions, as well as government statistical data. Regression analysis was used to examine the relationship between the factors affecting the financing of small and medium enterprises in the banking sector.The results showed that internal and external factors have a significant influence on the financing of small and medium enterprises in the banking sector.